3-Mercaptopyruvate Sulfurtransferase, Not Cystathionine β-Synthase Nor Cystathionine γ-Lyase, Mediates Hypoxia-Induced Migration of Vascular Endothelial Cells - Beibei Tao; Rui Wang; Chen Sun; Yichun Zhu (Frontiers Media S.A., 2017)
Hypoxia-induced angiogenesis is a common phenomenon in many physiological and patho-physiological processes. However, the potential differential roles of three hydrogen sulfide producing systems cystathionine γ-lyase (CSE)/H2S, cystathionine β-synthase (CBS)/H2S, and 3-mercaptopyruvate sulfurtransferase (MPST)/H2S in hypoxia-induced angiogenesis are still unknown. We found that minor hypoxia (10% oxygen) significantly increased the migration of vascular endothelial cells while hypoxia (8% oxygen) significantly inhibited cell migration. The present study was performed using cells cultured in 10% oxygen. RNA interference was used to block the endogenous generation of hydrogen sulfide by CSE, CBS, or MPST in a vascular endothelial cell migration model in both normoxia and hypoxia. The results showed that CBS had a promoting effect on the migration of vascular endothelial cells cultured in both normoxic and hypoxic conditions. In contrast, CSE had an inhibitory effect on cell migration. MPST had a promoting effect on the migration of vascular endothelial cells cultured in hypoxia; however, it had no effect on the cells cultured in normoxia. Importantly, it was found that the hypoxia-induced increase in vascular endothelial cell migration was mediated by MPST, but not CSE or CBS. The western blot analyses showed that hypoxia significantly increased MPST protein levels, decreased CSE protein levels and did not change CBS levels, suggesting that these three hydrogen sulfide-producing systems respond differently to hypoxic conditions. Interestingly, MPST protein levels were elevated by hypoxia in a bi-phasic manner and MPST mRNA levels increased later than the first stage elevation of the protein levels, implying that the expression of MPST induced by hypoxia was also regulated at a post-transcriptional level. RNA pull-down assay showed that some candidate RNA binding proteins, such as nucleolin and Annexin A2, were dissociated from the 3'-UTR of MPST mRNA in hypoxia which implied their involvement in MPST mRNA regulation.